2012
DOI: 10.1007/s00125-012-2648-4
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of gut microbiota by antibiotics improves insulin signalling in high-fat fed mice

Abstract: Aims/hypothesis A high-fat dietary intake induces obesity and subclinical inflammation, which play important roles in insulin resistance. Recent studies have suggested that increased concentrations of circulating lipopolysaccharide (LPS), promoted by changes in intestinal permeability, may have a pivotal role in insulin resistance. Thus, we investigated the effect of gut microbiota modulation on insulin resistance and macrophage infiltration. Methods Swiss mice were submitted to a high-fat diet with antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
196
5
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(228 citation statements)
references
References 44 publications
18
196
5
9
Order By: Relevance
“…In addition, as previously reported [19] , we also observed a systemic repression of inflammation by antibiotic treatment. A striking observation in this study was that antibiotic treatment exerted a dramatic effect in improving glucose intolerance in HFD-fed mice, which was comparable to that of metformin.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, as previously reported [19] , we also observed a systemic repression of inflammation by antibiotic treatment. A striking observation in this study was that antibiotic treatment exerted a dramatic effect in improving glucose intolerance in HFD-fed mice, which was comparable to that of metformin.…”
Section: Discussionsupporting
confidence: 91%
“…In concert with the role of gut bacteria and LPS on the regulation of host inflammation and insulin sensitivity, antibiotic treatment aiming to reduce gut-derived LPS [19] exerted similar effects to metformin in attenuating oxidative stress, activating the Nrf2 system and reducing PTEN expression. In addition, as previously reported [19] , we also observed a systemic repression of inflammation by antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased insulin sensivity following 1 week of vancomycin treatment was observed in humans following changes in gut microbiota and bile acids (34), whereas a retrospective study has reported increased adiposity following antibiotic treatment with vancomycin for infectious endocarditis (58). In contrast to these observations, exposure to antibiotics in early life among children of overweight mothers has been associated with a decreased risk of overweight in childhood (52) and studies of ob/ob, high-fat diet-fed and insulin-resistant mice have demonstrated improved glucose tolerance following antibiotic treatment (22,59). Collectively, these studies may suggest that exposure to antibiotics early in life on one hand has the potential to disturb a healthy gut microbiota but, on the other hand, also has the potential to modify a disturbed microbiota towards a healthier state.…”
Section: Type 2 Diabetes and Gut Microbiota: A Word Of Cautionmentioning
confidence: 99%
“…Moreover, mice treated with a high-fat diet, were observed to present a reduction in intestinal permeability and in serum LPS levels, in addition to a decrease in the inflammation of adipose tissue and macrophage infiltration, after the modification of gut microbiota using antibiotics (49)(50)(51)(52)(53).…”
Section: Induction Of Subclinical Inflammationmentioning
confidence: 99%